2019
DOI: 10.4236/aim.2019.911060
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Some Lactic Acid Bacteria Isolated from Selected Nigerian Fermented Foods for Vitamin Production

Abstract: Human vitamin deficiencies still occur in many countries although most vitamins are present in a variety of foods, mainly because of malnutrition not only as a result of insufficient food intake but also because of unbalanced diets; this work screens some Lactic acid bacteria isolated from selected Nigerian fermented foods for vitamin (thiamine, riboflavin and niacin) production. Five lactic acid bacteria were isolated from selected Nigerian fermented foods (yoghurt, ogi, ogiri, ugba). The isolated lactic acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…The presence of the three Lactic acid bacteria being Lactobacillus spp, Micrococcus spp, and Streptococcus spp as well as and Bacillus spp is not surprising as most of these thrive in medium rich in fermentable substrates like sugars, which often lead to the production of acids after fermentation as reported by [27], [26]. The absence of E. coli from the experimental samples could be due to the thorough washing and rinsing of the raw materials as well as the sterile water and strip aseptic procedures adopted in the production of the four experimental kunun zaki samples analyzed, supporting the work of [28]- [30].…”
Section: Microbial Loads Of the Kunun-zaki Samplesmentioning
confidence: 83%
“…The presence of the three Lactic acid bacteria being Lactobacillus spp, Micrococcus spp, and Streptococcus spp as well as and Bacillus spp is not surprising as most of these thrive in medium rich in fermentable substrates like sugars, which often lead to the production of acids after fermentation as reported by [27], [26]. The absence of E. coli from the experimental samples could be due to the thorough washing and rinsing of the raw materials as well as the sterile water and strip aseptic procedures adopted in the production of the four experimental kunun zaki samples analyzed, supporting the work of [28]- [30].…”
Section: Microbial Loads Of the Kunun-zaki Samplesmentioning
confidence: 83%
“…Isolation of LAB was done by modification of the previously used method (Ngene et al, 2019). Three g of each of the 200 samples of fermented oil bean seeds were ground and suspended in 10 mL of sterile 0.1% peptone solution.…”
Section: Isolation Of Lactic Acid Bacteriamentioning
confidence: 99%
“…Over recent decades, lactic acid bacteria (LAB) have received much attention due to the health-promoting properties of certain strains, called probiotics. They are normal inhabitants of the healthy gut microbiota as they improve the balance of the microbial community in the intestine, confer protection against potential pathogenic bacteria, prevent or cure intestinal diseases and present in numerous fermented food products (Ngene et al, 2019;Rijkers et al, 2011;Brown and Valiere, 2004;Adak et al, 2002). LAB are used in a wide range of fermented food, they play a critical role in food processing and spontaneous fermentation (Elayaraja et al, 2014); also, they have been shown to be a major potential for use in biopreservation due to the fact that they are generally recognized as safe (GRAS) status (Salem, 2012;Vignolo et al, 2008;Radha and Padmavathi, 2015).…”
Section: Introductionmentioning
confidence: 99%